XIAOMI'S BRAND IMAGE ANALYSIS OF CONSUMER PURCHASING DECISIONS IN JAKARTA - Durahman Marpaung (SEAN Institute, 2023)
The role of a brand image is very important in marketing smartphone products. And this research was conducted to find out and describe the influence of this on consumer purchasing decisions for a smartphone brand called Xiaomi in Jakarta. In this study, a sample of 100 informants or respondents was taken. The technique used in collecting the data is non-probability sampling which emphasizes purposive sampling method. The data obtained was taken by distributing questionnaires to the respondents. Then for the data analysis technique used is the PLS or Partial Least Square technique. According to the analysis, it was found that price and brand image have a significant and positive influence on consumer purchasing decisions. This is shown by the influence of affordable prices and also a good brand image , so that purchasing decisions from consumers will obviously be much better. The selling price also has a significant partial effect on the consumer's decision to buy the Xiaomi smartphone. Brand image also has a significant influence on the decision.